Apex - Naam, Ramez (Angry Robot, 2015)
Global unrest spreads through the world, lies set off shockwaves of anger, rippling from mind to mind. Riot police battle neurally-linked protestors, armies are mobilized, political orders fall. Nexus-driven revolution is here. Against this backdrop a new breed of post-human children are growing into their powers. And a once-dead scientist is closing in on her ultimate aim- to seize the planet's electronic systems, and re-forge everything in her image.